Sinkronisasi Pembelajaran Karakter Pondok Pesantren Bahrul Ulum Tambakberas Jombang Dalam Menghadapi Perkembangan Revolusi Industri 4.0 - Saputra, Hery; Hidayatulloh, Faisol; Huda, Saihul Atho Alaul (JoEMS (Journal of Education and Management Studies), 2022)
With the progress of the industrial revolution 4.0, it is not only the world of work that feels the impact, but the world of education feels it too. Where the decline in the character of students is the impact of industrial progress. From the existing problem, whether Islamic boarding schools are able to face the progress of the industrial revolution 4.0. The strategy adopted by the board of the Bahrul Ulum (Induk) Islamic boarding school in educating the character of the students is to provide a lot of activity programs to the students needed in the community, so that when the students leave the boarding school their characters are ready to face society in the era of industrial revolution 4.0. The research method uses descriptive qualitative. It can be concluded that character learning at the Pondok Pesantren Bahrul 'Ulum (Parent) Tambakberas Jombang is quite good, but not only the teacher should guide, but all administrators should also always try to guide and become role models for new students, because of the guidance of the administrators. is the main capital to achieve maximum results in the character of students to face the industrial revolution 4.0.